A Rare Clinical Case of Oral White Sponge Nevus and the Associated Challenges in Its Differential Diagnosis - E. Deliverska; Marusya Genadieva; B. Yordanov; J. Kirilova (Case Reports in Dentistry)
White sponge nevus is a rare genetic autosomal dominant disorder characterized by irregular patches of thick, white diffuse plaques, which mainly affects the oral mucosa and, very rarely, the skin or mucosa of the nose, esophagus, and anogenital region. We present a case of oral white sponge nevus in a 62-year-old woman, the differential diagnosis of which was of particular interest due to other similar white oral lesions, some of which are potentially malignant. The lesions were verified histologically. However, no treatment was performed due to the benign and asymptomatic nature of the lesions.